Multisystemic langerhans-cell histiocytosis with dominant lesions of the lung parenchyma - Javorac Jovan; Živanović Dejan; Ilić Miroslav; Milenković Ana (Sestrinska reč, 2020)
Langerhans cell histiocytosis (LCH) is a rare disease of unknown aetiology characterized by abnormal monoclonal proliferation of CD1a+/ CD207+ myeloid dendritic cells (Langerhans cells) in various organs, including bones, skin, lymph nodes, liver, lungs, central nervous system (CNS). Pulmonary Langerhans cell histiocytosis (PLCH) may occur as single-system disease or the lungs may be affected within a multisystemic disease. This paper presents cases of two patients with multisystemic LCH, with predominant lung involvement. In the first patient, the disease is in the terminal stage, with chronic respiratory failure requiring long-term oxygen therapy at home and development of severe pulmonary hypertension, so the lung transplantation may be considered as the only potentially effective therapeutic procedure at this moment. The second patient is in the initial stage of the disease, with satisfactory pulmonary function for now, so it could be considered to use some new targeted therapy to prevent the progression of the disease. Thus, it is essential to consistently apply, as soon as possible, all available pharmacological treatments, as well as adequate palliative and health care, to ensure a decent quality of life for these patients.